Vejrforholdene i landbrugsåret 1949—50.(Fra 1. oktober 1949—30. september 1950.) - Krogsriis, C. A. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i landbrugsåret 1949—50.(Fra 1. oktober 1949—30. september 1950.)